Analisis Konflik Arab Spring di Suriah - Muhammad Ridho; Yanyan Muhammad Yani; Arfin Sudirman (Universitas Negeri Medan, 2020)
This study aim to explain phenomenon of Arab spring that occurred in Syria and describing the triggering factors of conflict Syria and the analysis of Alawie group in Syria. The type of this study uses a qualitative approach with the literature study method, because the data collection techniques used make books and documents related to the Arab spring in Syria as a reference frame, as well as some data from a valid website. Data analysis techniques through three components, namely data reduction, data presentation and drawing conclusions in which data verification is also accompanied by triangulation of data sources. The results showed that the phenomenon of Arab spring that occurred in Syria converged on inter-ethnic conflict that occurred between the Sunni-Alawie, then triggered by the phenomenon of Arab spring that spread in the Middle East.